2017
DOI: 10.1038/s41598-017-01305-2
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and its metabolites protect human melanocytes against UVB-induced damage: Involvement of NRF2-mediated pathways

Abstract: Ultraviolet light (UV) is an inducer of reactive oxygen species (ROS) as well as 6-4-photoproducts and cyclobutane pyrimidine dimers (CPD) in the skin, which further cause damage to the skin cells. Irradiation of cultured human melanocytes with UVB stimulated ROS production, which was reduced in cells treated with melatonin or its metabolites: 6-hydroxymelatonin (6-OHM), N1-acetyl-N2-formyl-5-methoxykynuramine (AFMK), N-acetylserotonin (NAS), and 5-methoxytryptamine (5-MT). Melatonin and its derivatives also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
183
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(206 citation statements)
references
References 62 publications
11
183
2
3
Order By: Relevance
“…Similar effect was observed for keratinocytes, melanocytes, and dermal fibroblasts in culture [33, 55, 56]. Furthermore, melatonin derivative AMK was found to be potent singlet oxygen scavenger [57].…”
Section: Physiological Role Of Melatonin and Metabolites In The Skinmentioning
confidence: 59%
See 2 more Smart Citations
“…Similar effect was observed for keratinocytes, melanocytes, and dermal fibroblasts in culture [33, 55, 56]. Furthermore, melatonin derivative AMK was found to be potent singlet oxygen scavenger [57].…”
Section: Physiological Role Of Melatonin and Metabolites In The Skinmentioning
confidence: 59%
“…We have reported protective effects of melatonin and its metabolites: 6-hydroxymelatonin, AFMK, N -acetyl-serotonin, and 5-methoxytryptamine in reducing oxidative cell damage in human skin cells: keratinocytes and melanocytes, elicited by UVB [55, 56]. Pharmacological doses of melatonin and its derivatives protect both type of cells, keratinocytes and melanocytes, from UVB-induced oxidative stress.…”
Section: Physiological Role Of Melatonin and Metabolites In The Skinmentioning
confidence: 99%
See 1 more Smart Citation
“…It acts as an antioxidant by reducing oxidative stress and increasing the activity of antioxidant enzymes in the body [20]. Melatonin protects melanocytes from DNA damage and oxidative stress through activation of NRF2 and its target enzymes [21]. It is well reported that melatonin can ameliorate ischaemic brain injury, preserve the functional integrity of the blood-brain barrier, and induce neurogenesis and cell proliferation through a receptor-dependent mechanism [22].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, it was shown that UVB-induced damage is mediated almost solely by ROS generation in the skin [30, 31]. In addition, several publications reported that UV radiation can be attenuated by activating the Nrf2 signaling pathway [32-36].…”
Section: Resultsmentioning
confidence: 99%